Advances in Stored Product Protection. Proceedings of the 8th International Working Conference on Stored Product Protection, Yo 2003
DOI: 10.1079/9780851996912.0888
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on the efficacy of spinosad dust against major storage insect pests.

Abstract: Laboratory bioassays were conducted to compare the efficacy of spinosad dust (0.125%) admixed with shelled wheat grains with that of a cocktail of pirimiphos-methyl (1.6%) and permethrin (0.3%) as actellic super dust against Sitophilus zeamais, Tribolium castaneum, Rhyzopertha dominica and Prostephanus truncatus. Spinosad dust was applied at 0.35, 0.7 and 1.44 ppm, and actellic dust at 10.5 ppm. All treatments were significantly (P=0.05) better than the control except when applied against T. castaneum. Spinosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 0 publications
1
11
0
3
Order By: Relevance
“…Similarly, Mutambuki et al (2003) noted that P. truncatus was also very susceptible to dry spinosad. According to Athanassiou et al (2008b), P. truncatus was proved very susceptible to liquid spinosad, at dose rates as low as 0.1 ppm.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Mutambuki et al (2003) noted that P. truncatus was also very susceptible to dry spinosad. According to Athanassiou et al (2008b), P. truncatus was proved very susceptible to liquid spinosad, at dose rates as low as 0.1 ppm.…”
Section: Discussionmentioning
confidence: 94%
“…However, most of the available data concern the application of liquid spinosad formulations, while there is a paucity of information on the use of dry (dust) spinosad. Mutambuki et al (2003) reported that spinosad dust was effective in maize against Prostephanus truncatus (Horn), Sitophilus zeamais Motschulsky and Tribolium castaneum (Herbst).…”
Section: Introductionmentioning
confidence: 98%
“…truncatus to spinosad. Mutambuki et al ( 2003 ) tested spinosad against P . truncatus in semi-field tests in Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Spintor ® is a 0.125% spinosad dust formulation that was first registered in Kenya in 2003 as a grain protectant (Mutambuki et al, 2012) and has since been registered in more than 15 African countries for domestic use only, with no export of Spintor ® treated grain (Hertlein et al, 2011). Maize cob and red haricot bean trash (remains of the plant after seed has been threshed) were separately burned on sheet metal and then passed across a sieve of 1 mm aperture size to obtain dust with uniform particle size.…”
Section: Grain Protectantsmentioning
confidence: 99%